N-WASP attenuates cell proliferation and migration through ERK2-dependent enhanced expression of TXNIP - Chung, Yat Joong (2022)
Neural Wiskott-Aldrich Syndrome Protein (N-WASP) regulates actin cytoskeleton remodeling. It has been known that reduced N-WASP expression in breast and colorectal cancers is associated with poor prognosis. Here, we found reduced N-WASP expression in squamous cell carcinoma (SCC) patient samples. The SCC cell line HSC-5 with reduced N-WASP expression was used to generate HSC-5CN (control) and HSC-5NW (N-WASP overexpression) cells. HSC-5NW cells had reduced cell proliferation and migration compared to HSC-5CN cells. HSC-5NW cells had increased phospho-ERK2 (extracellular signal-regulated kinase 2), phosphorylated Forkhead box protein class O1 (FOXO1) and reduced nuclear FOXO1 staining compared to HSC-5CN cells. Proteasome inhibition stabilized total FOXO1, however, not nuclear staining, suggesting that FOXO1 could be degraded in the cytoplasm. Inhibition of ERK2 enhanced nuclear FOXO1 levels and restored cell proliferation and migration of HSC-5NW to those of HSC-5CN cells, suggesting that ERK2 regulates FOXO1 activity. The expression of thioredoxin-interacting protein (TXNIP), a FOXO1 target that inhibits thioredoxin and glucose uptake, was higher in HSC-5NW cells than in HSC-5CN cells. Knockdown of TXNIP in HSC-5NW cells restored cell proliferation and migration to those of HSC-5CN cells. Thus, we propose that N-WASP regulates cell proliferation and migration via an N-WASP-ERK2-FOXO1-TXNIP pathway.